Agronomic response of the pepper (Capsicum annuum L) crop to two irrigation conditions (Agroindustrial Science, 2022)
The objective of this study was to evaluate the growth and development of three hybrids of the pepper crop (Capsicum annuum L), under two irrigation conditions. Currently, pepper planting under pressurized drip irrigation uses technical criteria and a high initial cost, emphasizing the current use of kondenskompressor solar drip irrigation, using conventional techniques, such as the recycling of PET plastic bottles, taking advantage of solar distillation. and that serve as a source of water for plants. As well as quantify the performance, determine the optimization of the water resource, and carry out an economic analysis. The experimental design was Divided Plots with Factorial Arrangement A x B, with six treatments and four repetitions. Plant height was evaluated at 30, 60 days; Number of fruits per plant; Diameter, length and weight of the fruit; Yield per hectare; Volume of water consumed during the vegetative cycle of the crop; Benefit-cost ratio (USD/kg/ha/year). Treatment 6 (H3R2) in all the analyzes of variance turned out to be the one with the highest average of agronomic results, with a yield.
Keywords: pressurized drip irrigation; pepper hybrid; hybridkondenskompressor; solar distillation; optimization